Improving Public Services Based on E-Government at the Population and Civil Registration Office of Gresik Regency - Apri Widyastik; Amirul Mustofa; Ulul Albab; Sri Kamariyah (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This study aims to analyze the implementation of e-government in improving the quality of public services at the Population and Civil Registration Office of Gresik Regency. The study uses a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The analysis focuses on the stages of e-government implementation, covering the dimensions of presence, interaction, and transaction in population administration services. The results indicate that the implementation of e-government at the Population and Civil Registration Office of Gresik Regency has been carried out through the provision of digital information media, such as an official website and online-based population administration service applications. In the presence dimension, the local government provides various information related to population administration services, including requirements, procedures, service times, and the types of services available to the public. In the interaction dimension, the digital service system allows the public to communicate with the service office by submitting questions, complaints, or requests for information online. Meanwhile, in the transaction dimension, the public can submit requests for population documents, such as Family Cards, birth certificates, and other documents, through the digital service system. The implementation of e-government has positively impacted the efficiency, transparency, and ease of access to population administration services for the public. Therefore, the utilization of information technology in public services can serve as an important strategy for improving the quality of population administration services in local government.